Cyclic events of spermatogenic cells in the seminiferous tubules of Guinea pigs - Abdul-Hadi S. Mohammed; Widad A. Jawad (Kufa Journal for Veterinary Medical Sciences, 2010)
There are  twelve stages were identified in the spermatogenic cycle  in Guinea Pig, each contains one or two generations of spermatids which is connected with one or two generations of Spermatocytes and one or two generations of spermatogonia. This cycle leads into the formation of significant changes in the diameter and height of the epithelium of the seminiferous tubules which reaches its highest(59.78 + 0.07 micrometer) and (215.3+0.08micrometer) in diameter at the seventh stage . Also the least hight of epithelium (49.42+ 0.09micrometer) is   realized at the eleventh stage,and the least diameter (195.39+0.08 micrometer) at the ninth stage. statistical analysis indicated significant differences (p<0.05) between the different stages of the spermatogenic cycle.